Rhythm Explorers: Creative Approach in Drum Learning for Elementary Students in Private Music Education - Piter Sembiring; Rita Milyartini (Universitas Muhammadiyah Mataram, 2025)
This study explores a creative approach to drumming instruction for primary school students in private music education institutions, aiming to enhance rhythmic ability through improvisation and exploration of complex rhythmic patterns. A qualitative research design was employed, involving twelve purposively selected students of varying ages. Data were collected through in-depth interviews, direct observation, and documentation. The findings indicate that integrating games and challenges into drumming lessons improves rhythmic accuracy, creativity, and motor coordination. The approach also supports emotional and cognitive development by encouraging self-expression through music. Key outcomes include increased technical mastery, stronger self-confidence, and greater adaptability to complex rhythms. Although implementation faced challenges such as limited infrastructure and psychological barriers among students, applied solutions contributed to a more engaging and effective learning environment.